Effects of end-of-life care on medical health professionals: A dialectical approach. Issue 1 (February 2022) - Stokar, Yaffa Naomi; Pat-Horenczyk, Ruth
Abstract: Objective: The provision of end-of-life (EOL) care has complex effects on both the professional and personal well-being of medical health personnel (MHP). Previous studies have mostly focused on negative or positive influences as mutually exclusive effects. This study offers a new conceptualization by applying a dialectical lens, looking at secondary traumatic stress (STS) and post-traumatic growth (PTG) as dual possible coexisting phenomena. The creation of four theoretically possible profiles, based on the combinations of high or low levels in each dimension, offers a practical translation of this idea toward intervention development. Method: Data were collected at a large tertiary pediatric medical center ( n = 1, 123) aiming at assessing all personnel. Research methods included collecting demographic data and using validated scales to assess STS, PTG, burnout, compassion satisfaction, and both personal and professional social support. Results: We classified four response profiles according to the STS and PTG levels: (1) Dialectical-impact, high STS/high PTG, (2) Growth-dominant, high PTG/low STS, (3) Stress-dominant, high STS/low PTG, and (4) Limited-impact, low STS/low PTG. The four profiles differed based on profession, but not other demographics. Physicians were represented significantly higher in the Stress-dominant profile; nurses were highly represented in the Dialectical-impact profile. A significant difference was found when adding reported EOL care as a distinct factor with a higher relative proportion of the "dialectical" response among those reporting providing EOL care. Significance of results: Findings from this study point toward the recognition and understanding of the complexity resulting from the provision of EOL care. A more complex profile classification, including the dialectical profile, may reflect a broader tendency to ways that MHP are affected by their work. Introducing "dialectical thinking" can lead to more personalized and precise intervention planning for MHP. Tailored interventions promoting personal and professional well-being, based on individual profiles, can contribute to more effective interventions and better resource utilization.